Pre-Adolescent Cardio-Metabolic Associations and Correlates: PACMAC methodology and study protocol. Issue 9 (18th September 2014) - Castro, Nicholas; Faulkner, James; Skidmore, Paula; Williams, Michelle; Lambrick, Danielle M; Signal, Leigh; Thunders, Michelle; Muller, Diane; Lark, Sally; Hamlin, Mike; Lane, Andrew M; Kingi, Te Kani; et al.
Abstract : Introduction: Although cardiovascular disease is typically associated with middle or old age, the atherosclerotic process often initiates early in childhood. The process of atherosclerosis appears to be occurring at an increasing rate, even in pre-adolescents, and has been linked to the childhood obesity epidemic. This study will investigate the relationships between obesity, lifestyle behaviours and cardiometabolic health in pre-pubescent children aged 8–10 years, and investigates whether there are differences in the correlates of cardiometabolic health between Māori and Caucasian children. Details of the methodological aspects of recruitment, inclusion/exclusion criteria, assessments, statistical analyses, dissemination of findings and anticipated impact are described. Methods and analysis: Phase 1: a cross-sectional study design will be used to investigate relationships between obesity, lifestyle behaviours (nutrition, physical activity/fitness, sleep behaviour, psychosocial influences) and cardiometabolic health in a sample of 400 pre-pubescent (8–10 years old) children. Phase 2: in a subgroup (50 Caucasian, 50 Māori children), additional measurements of cardiometabolic health and lifestyle behaviours will be obtained to provide objective and detailed data. General linear models and logistic regression will be used to investigate the strongest correlate of (1) fatness; (2) physical activity; (3) nutritional behaviours and (4) cardiometabolic health. Ethics and dissemination: Ethical approval will be obtained from the New Zealand Health and Disabilities Ethics Committee. The findings from this study will elucidate targets for decreasing obesity and improving cardiometabolic health among preadolescent children in New Zealand. The aim is to ensure an immediate impact by disseminating these findings in an applicable manner via popular media and traditional academic forums. Most importantly, results from the study will be disseminated to participating schools and relevant Māori health entities.